Construção de uma tipologia funcional de gramíneas em pastagens naturais sob diferentes manejos - Garagorry, Fabio Cervo (2008)
Plant functional types defined from morphological attributes are fundamental to understanding functioning of grasslands communities. Thus, to build a classification based solely on grasses (family of greater biomass contribution), it is necessary for increasing the knowledge about complex ecosystems. This work aims to characterize vegetation dynamics by species and by functional types of grasses of two RS physiographic regions (Depressão Central-Santa Maria and Campanha-Bagé) under different managements. The evaluated treatments were: natural pasture and natural pasture overseeded with cool season species (Bagé) and natural pasture submitted to burning and grazing treatments (Santa Maria). For this, permanent transects were used in order to represent the different communities at paddock level. Vegetation dynamics was evaluated using procedures of BOTANAL method. Tillers of grasses with contributions exceeding 3% of total aboveground biomass were collected for subsequent measurement of the attributes specific leaf area (AFE) and leaves dry matter content (TMS). Burned treatments presented greater contribution of Andropogon lateralis, while in grazed treatments there was a greater species diversity. Introduction of cool season species combined with fertilizer promotes an increase of species characterized by resources´ capture. TMS was more stable for species linked to capturing resources strategy and AFE was more robust for species characterized by resources conservation. Therefore, until a regional data basis were developed, it is recommended to use both attributes for future research.